Native American Ancestry, Lung Function, and COPD in Costa Ricans - Chen, Wei (American College of Chest Physicians, 2014)
BACKGROUND: Whether Native American ancestry (NAA) is associated with COPD or lung function in a racially admixed Hispanic population is unknown. METHODS: We recruited 578 Costa Ricans with and without COPD into a hybrid case-control/family-based cohort, including 316 members of families of index case subjects. All participants completed questionnaires and spirometry and gave a blood sample for DNA extraction. Genome-wide genotyping was conducted with the Illumina Human610-Quad and HumanOmniExpress BeadChip kits (Illumina Inc), and individual ancestral proportions were estimated from these genotypic data and reference panels. For unrelated individuals, linear or logistic regression was used for the analysis of NAA and COPD (GOLD [Global Initiative for Chronic Obstructive Lung Disease] stage II or greater) or lung function. For extended families, linear mixed models and generalized estimating equations were used for the analysis. All models were adjusted for age, sex, educational level, and smoking behavior; models for FEV(1) were also adjusted for height. RESULTS: The average proportion of European, Native American, and African ancestry among participants was 62%, 35%, and 3%, respectively. After adjustment for current smoking and other covariates, NAA was inversely associated with COPD (OR per 10% increment, 0.55; 95% CI, 0.41-0.75) but positively associated with FEV(1), FVC, and FEV(1)/FVC. After additional adjustment for pack-years of smoking, the association between NAA and COPD or lung function measures was slightly attenuated. We found that about 31% of the estimated effect of NAA on COPD is mediated by pack-years of smoking. CONCLUSIONS: NAA is inversely associated with COPD but positively associated with FEV(1) or FVC in Costa Ricans. Ancestral effects on smoking behavior partly explain the findings for COPD but not for FEV(1) or FVC.